Efisiensi Produksi Susu Sapi Perah Di Kelompok Peternak Mandiri Sejahtera Desa Tajurhalang Kabupaten Bogor - Yuniawan Yuniawan; Samaiharuh Samaiharuh (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2022)
This research aims to know efficiency of milk production at Mandiri Sejahtera Dairy Farmers Group and also to know how the factors of milk productions influence the amount of milk production at that group. Research methode which is used is with using giving quiz containing questions about factors relating to milk production. Factors of milk production which are researched are ownership of dairy cow for every farmer (SL), forage (H) and concentrate (K) which is used for every month/dairy cow, and working time per month/dairy cow. Data analysis used is using Cobb Douglass Equation, so, We could get milk production equation and know factors which significant (P < 0,01 atau P < 0,05) influence to milk production. Cobb Douglas Function of that milk production is LnPS = 0,38 + 0,432 LnH - 0,263 LnK + 0,590 LnJ* + 0,941 LnSL**. Factors most significant (P < 0,01) influence the milk production are the ownership of dairy cow. The ownership of dairy cow which is efficient is about 3,32 LU/month/farmer which could produce milk about 250 liter/month/farmer. Keywords: Milk Production, Cobb Douglass, Ownership Of Dairy Cow, Dairy Farmer